Analisis Success Full Call Ratio Network Telecommunication pada Global System For Mobile Communication (GSM) PT.Telkomsel RTPO Berau - Hadawina Hadawina; Rahmania Rahmania; Ridwang Ridwang; Rizki Yusliana Bakti; Muhyiddin A M Hayat (Ainet : Jurnal Informatika, 2021)
This GSM network stands for Global System for Mobile Communications, which is a digital mobile communication technology, especially in mobile phones. Currently, almost all mobile telecommunicaions instrumentation uses cellular-based technology. Cellular-based mobile telecommunications systems offer advantages compared to wireless systems, namely mobility so that users can move anywhere as long as they are still within the operator's service coverage. The purpose of this study was to measure and analyze how the GSM (Global System For Mobile Communications) network performance of a BTS at PT.Telekomunikasi RTPO Berau during 2020 was based on the results of the analysis of CSSR, CDR, HOSR, TCHCR values. The results showed that the GSM network performance of a BTS at PT. Telecommunications RTPO Berau. The performance results in the first BTS with CSSR values = 99.31%, CDR = 0.30%, HOSR = 94.74%, TCHCR = 0.01%, and for the second BTS performance values CSSR = 98.66%, CDR = 0.35%, HOSR = 96.78%, TCHCR = 0%, and the third BTS with CSSR = 99.74%, CDR = 0.03%, HOSR = 98.01%, TCHCR = 0%. Based on the results of the analysis of the performance of the GSM network in the Berau area and compared with the standard parameters of the KPI (Key Performance Indicator) it can be concluded that the performance of the GSM network in the three BTS is good.